Missing self-recognition of Ocil/Clr-b by inhibitory NKR-P1 natural killer cell receptors - Carlyle, James R. (National Academy of Sciences, 2004)
The NKR-P1 family of C-type lectin-like receptors are expressed on natural killer (NK) cells and NKT cells. We report the cloning and characterization of a cognate ligand for the inhibitory mouse NK receptors (NKR)-P1B and NKR-P1D (CD161b/d). The NKR-P1B/D ligand is osteoclast inhibitory lectin (Ocil), also known as Clr-b, a member of a previously cloned group of C-type lectin-related (Clr) proteins linked to the NKR-P1 receptors in the mouse NK gene complex (NKC). Expression of Ocil/Clr-b on mouse tumor cell lines inhibits NK cell-mediated killing. Inhibition is blocked with a new mAb (4A6) specific for Ocil/Clr-b. By using 4A6 mAb, we demonstrate that Ocil/Clr-b is displayed at high levels on nearly all hematopoietic cells, with the exception of erythrocytes, in a pattern that is similar to that of class I MHC molecules. Remarkably, Ocil/Clr-b is frequently down-regulated on mouse tumor cell lines, indicating a role for this receptor-ligand system in a new form of “missing self-recognition” of tumor cells.